The Effect of Beverages and Polishing on Discoloration of Different Provisional Prosthetic Materials: An in Vitro Study - Rençber Kizilkaya, Ayşe; Dursun, Meltem Nermin (Selcuk University, 2023)
Objective: The aim of this study was to evaluate the effect of five different beverages and polishing on the color change of two different temporary prosthetic materials manufactured with different methods. Method: 160 (10x2 mm) disc-shaped samples were fabricated using direct (Acrytemp)(n=80) and indirect (Imident) (n=80) temporary prosthetic materials. Samples prepared using molds were divided into four groups as polished (direct/indirect material) and unpolished (direct/indirect material) (n=40 each). After initial measurement of L,a,b values using a spectrophotometer, the samples in each group were immersed in five different beverages (distilled water (DW), coffee (CF), cola (CC), sour cherry juice (CJ), red wine (RW) (n=8) and stored for 7 days. Then, the spectrophotometric measurements of the samples were repeated and the color change (?E00) values were calculated. Data were analyzed using a three-way-ANOVA followed by post hoc Tukey HSD test (p=0.05). Results: Greater color change was observed in the direct temporary material (p<0.05). A statistically significant difference was found between polished and unpolished samples (p<0.05). There was no significant difference between indirect and direct temporary materials in terms of discoloration in the CC and DW groups (p>0.05). Indirect temporary material exhibited less color change than their direct counterparts in the RW, CJ, CF groups (p<0.05). Less color change was observed in the polished groups (except DW) in direct temporary materials (p<0.05). Color change values were lower in the CC and DW groups compared to CF group (p<0.05). Comparing the direct temporary material groups, the greatest color change value was found in the RW group (p<0.05). Conclusion: Although variations in color change can be observed depending on the contents of the temporary materials and the beverages utilized, surface polishing of the material contributes to a reduction in color change. © 2023, Selcuk University. All rights reserved.
İçeceklerin ve Polisajın Farklı Geçici Protetik Materyallerin Renk Değişimine Etkisi: in Vitro Çalışma
Keywords: Bis-acryl; Color stability; Polishing; Polymethylmethacrylate; Temporary prosthetic materials